Reorganization of the Brain Structural Covariance Network in Ischemic Moyamoya Disease Revealed by Graph Theoretical Analysis - Wang, Peijing; Li, Wenjie; Zhu, Huan; Liu, Xingju; Yu, Tao; Zhang, Dong; Zhang, Yan (Frontiers in Aging Neuroscience, 2022)
Objective: Ischemic moyamoya (MMD) disease could alter cerebral structure, but little is known about the topological organization of structural covariance network (SCN). This study employed structural magnetic resonance imaging and graph theory to evaluate SCN reorganization in ischemic MMD patients. Method: Forty-nine stroke-free ischemic MMD patients and 49 well matched healthy controls (HCs) were examined by T1-MPRAGE imaging. Structural images were pre-processed using the Computational Anatomy Toolbox 12 (CAT 12) based on the DARTEL algorithm and both the global and regional SCN parameters were calculated and compared using Graph Analysis Toolbox (GAT). Results: Characteristic path length (Lp), clustering coefficient (Cp), assortativity, local efficiency and transitivity, most of the important metrics of global network organization, were significantly reduced in MMD patients compared to HCs. In addition, the regional betweenness centrality (BC) values of the bilateral medial orbitofrontal cortices were significantly lower in MMD patients than HCs after false discovery rate (FDR) correction for multiple comparisons. The BC was also reduced in the left medial superior frontal gyrus and hippocampus, and increased in the bilateral middle cingulate gyri of patients, but these differences were not significant after FDR correlation. No differences in network resilience were detected by targeted attack analysis or random failure analysis. Conclusions: Both global and regional properties of the SCN are altered in MMD, even in the absence of major stroke or hemorrhagic damage. Patients exhibit a less optimal and more randomized SCN than HCs, and the nodal BC of the bilateral medial orbitofrontal cortices is severely reduced. These changes may account for the impairments in memory, emotional regulation, and executive function observed in MMD.